1977
DOI: 10.1002/1097-4679(197704)33:2<555::aid-jclp2270330248>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Pain adaptation and emotional deficit

Abstract: The pain adaptation rates of high- and low-emotional deficit schizophrenics were compared. Electrical stimulation pain thresholds were calculated and retaken at four intervals after administration of shocks in a learning task. Low scorers on the General Sensation-Seeking and Thrill/Adventure Seeking scales showed significantly less pain adaptation than did their high sensation-seeking counterparts. No differences in level of adaptation appeared between high and low scorers on the Anhedonia scale or three other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Different types of painful stimuli have been investigated and patients’ responses to pain have been assessed and analyzed using a variety of methods. Studies have examined the responses of patients with schizophrenia to thermal pain (Malmo et al 1951; Hemphill et al 1952; Hall and Stride 1954; Kane et al 1971; Clark and Mehl 1976; Dworkin et al 1993 a ), electrical pain (Bender and Schilder 1930; Parsons et al 1949; Collins and Stone 1966; Ax et al 1970; Sappington 1973; Watson and Jacobs 1977; Davis et al 1979 b ; Ingvar 1980; Buchsbaum et al 1984, 1986), cold-pressor pain (Earle and Earle 1955; Maricq and Edelberg 1975; Albus et al 1982), pin-prick and pressure pain (Stengel et al 1955; Merskey et al 1962), painful pinch (May 1948), and imagined painful situations (Petrovich 1960). On the basis of verbal, avoidance, and/or psychophysiological measures, it has typically been reported that patients with schizophrenia have reduced sensitivity to pain.…”
mentioning
confidence: 99%
“…Different types of painful stimuli have been investigated and patients’ responses to pain have been assessed and analyzed using a variety of methods. Studies have examined the responses of patients with schizophrenia to thermal pain (Malmo et al 1951; Hemphill et al 1952; Hall and Stride 1954; Kane et al 1971; Clark and Mehl 1976; Dworkin et al 1993 a ), electrical pain (Bender and Schilder 1930; Parsons et al 1949; Collins and Stone 1966; Ax et al 1970; Sappington 1973; Watson and Jacobs 1977; Davis et al 1979 b ; Ingvar 1980; Buchsbaum et al 1984, 1986), cold-pressor pain (Earle and Earle 1955; Maricq and Edelberg 1975; Albus et al 1982), pin-prick and pressure pain (Stengel et al 1955; Merskey et al 1962), painful pinch (May 1948), and imagined painful situations (Petrovich 1960). On the basis of verbal, avoidance, and/or psychophysiological measures, it has typically been reported that patients with schizophrenia have reduced sensitivity to pain.…”
mentioning
confidence: 99%